Memorable Tourism Experience (MTE): a scale proposal and test - Coelho,Mariana de Freitas (2018)
This paper aims to propose and test a scale to assess Memorable Tourism Experiences (MTE). It presents an instrument initially containing 49 tested items, organised into 12 dimensions: Environment, Culture, Relationship with Companions, Relationship with Tourists, Relationship with Local Agents (residents and service providers), Novelty, Emotions, Dream, Meaningfulness, Refreshment, Hedonism and Involvement. Data collection included a survey of 1,193 Brazilians with regular travel habits, aged from 18 years old. Data were analysed quantitatively via Structural Equation Modelling. Statistical tests of Exploratory Factor Analysis (EFA) followed the Confirmatory Factor Analysis (CFA). The results indicate that the scale is reliable and valid for the study of MTEs, at least for the studied sample. It attests to the multidimensionality of MTE construct, but Hedonism and Involvement are not appropriate dimensions. Thus, it confirmed the validity of the new MTE scale consisting of 35 items and ten dimensions of the second- order construct.